Impact of enterovirus and other enteric pathogens on oral polio and rotavirus vaccine performance in Bangladeshi infants. Issue 27 (8th June 2016) - Taniuchi, Mami; Platts-Mills, James A.; Begum, Sharmin; Uddin, Md Jashim; Sobuz, Shihab U.; Liu, Jie; Kirkpatrick, Beth D.; Colgate, E. Ross; Carmolli, Marya P.; Dickson, Dorothy M.; Nayak, Uma; Haque, Rashidul; et al.
Highlights: Oral vaccines exhibit poor performance in low-income settings. Enterovirus and Campylobacter carriage are associated with lower OPV immunogenicity. Enterovirus carriage is associated with lower Rotarix immunogenicity and efficacy. Abstract: Background: Oral polio vaccine (OPV) and rotavirus vaccine (RV) exhibit poorer performance in low-income settings compared to high-income settings. Prior studies have suggested an inhibitory effect of concurrent non-polio enterovirus (NPEV) infection, but the impact of other enteric infections has not been comprehensively evaluated. Methods: In urban Bangladesh, we tested stools for a broad range of enteric viruses, bacteria, parasites, and fungi by quantitative PCR from infants at weeks 6 and 10 of life, coincident with the first OPV and RV administration respectively, and examined the association between enteropathogen quantity and subsequent OPV serum neutralizing titers, serum rotavirus IgA, and rotavirus diarrhea. Results: Campylobacter and enterovirus (EV) quantity at the time of administration of the first dose of OPV was associated with lower OPV1-2 serum neutralizing titers, while enterovirus quantity was also associated with diminished rotavirus IgA (−0.08 change in log titer per tenfold increase in quantity; P  = 0.037), failure to seroconvert (OR 0.78, 95% CI: 0.64–0.96; P  = 0.022), and breakthrough rotavirus diarrhea (OR 1.34, 95% CI: 1.05–1.71; P  = 0.020) after adjusting for potential confounders. These associations were not observed for Sabin strain poliovirus quantity. Conclusion: In this broad survey of enteropathogens and oral vaccine performance we find a particular association between EV carriage, particularly NPEV, and OPV immunogenicity and RV protection. Strategies to reduce EV infections may improve oral vaccine responses. ClinicalTrials.gov Identifier:NCT01375647 .